In-Situ Elucidation of Probabilistic Gas Evolution Pathways in Thermal-Driven Degradation of LiFePO₄ Batteries - Mine Zhang; Wencin Teng; Lehuin Jiang; Rein Sun (Gio Vani Publisher, 2026)
Lithium-ion batteries are increasingly utilized to meet modern energy storage demands for high performance and sustainability. Despite their strong thermal stability, lithium iron phosphate (LiFePO₄) batteries face safety challenges from flammable gas emissions during thermal runaway. This study systematically examines gas evolution pathways through in-situ analysis and structural characterization of the LiFePO₄ cathode, identifying six key reactions driving thermal degradation. Results show that ethylene and carbon dioxide are the main gases produced, primarily from electrolyte decomposition. Diethyl carbonate undergoes evaporation and degradation, while ethylene carbonate reacts with active electrode materials. Although cathode structural changes occur under heat, no direct oxygen release was observed. The main causes of thermal runaway are anode–electrolyte reactions generating heat and gases between 200–300°C. Correlation analysis further indicates that hydrogen formation results from interactions between metallic lithium and trace water in a reductive environment. These findings enhance understanding of degradation chemistry and support the design of next-generation LiFePO₄ batteries with improved thermal safety.